High‐resolution data assimilation of cardiac mechanics applied to a dyssynchronous ventricle. (2nd April 2017) - Balaban, Gabriel; Finsberg, Henrik; Odland, Hans Henrik; Rognes, Marie E.; Ross, Stian; Sundnes, Joakim; Wall, Samuel
Abstract: Computational models of cardiac mechanics, personalized to a patient, offer access to mechanical information above and beyond direct medical imaging. Additionally, such models can be used to optimize and plan therapies in‐silico, thereby reducing risks and improving patient outcome. Model personalization has traditionally been achieved by data assimilation, which is the tuning or optimization of model parameters to match patient observations. Current data assimilation procedures for cardiac mechanics are limited in their ability to efficiently handle high‐dimensional parameters. This restricts parameter spatial resolution, and thereby the ability of a personalized model to account for heterogeneities that are often present in a diseased or injured heart. In this paper, we address this limitation by proposing an adjoint gradient–based data assimilation method that can efficiently handle high‐dimensional parameters. We test this procedure on a synthetic data set and provide a clinical example with a dyssynchronous left ventricle with highly irregular motion. Our results show that the method efficiently handles a high‐dimensional optimization parameter and produces an excellent agreement for personalized models to both synthetic and clinical data. Abstract : We propose an efficient adjoint gradient–based data assimilation method for high‐dimensional parameters in cardiac mechanics. We test this procedure on a synthetic data set and then fit a computational model to a clinical example of a dyssynchronous left ventricle with highly irregular motion.